Evaluation of Hysterosalpingographic Findings among Patients Presenting with Infertility - Ayyub, Rabia; Zulfiqar, Saima; Tahir, Umm E Farwa; Jamil, Muhammad Irfan (Indus Journal of Bioscience Research, 2025)
Aim and Background: Hysterosalpingography (HSG) is routinely employed in evaluating infertility to detect uterine and tubal abnormalities. This study aimed to determine the frequency and types of hysterosalpingographic abnormalities among women presenting with primary and secondary infertility. Material and Method: A descriptive cross-sectional study was conducted from December 2024 to May 2025 at Sheikh Zayed Hospital, Rahim Yar Khan. A total of 103 women aged 18-40 years, experiencing infertility for ≥12 months, underwent HSG. Abnormalities assessed included uterine fibroids, adhesions, congenital anomalies, hydrosalpinx, and tubal occlusion. Data analysis employed SPSS version 26. Results: Mean age was 29.7 ± 5.1 years, with average infertility duration of 3.8 ± 2.4 years. Primary infertility was observed in 61 (59.2%) and secondary in 42 (40.8%) women. Overall, 80 (77.7%) had abnormal HSG findings, significantly higher in secondary (88.1%) versus primary infertility (70.5%; p=0.031). Uterine abnormalities occurred in 33 (32%), including fibroids 14 (13.6%), polyps or adhesions 8 (7.8%), congenital anomalies 5 (4.9%), and Asherman’s syndrome 6 (5.8%). Tubal pathology was identified in 54 (52.4%) women, including tubal occlusion 41 (39.8%), bilateral occlusion 18 (17.5%), unilateral occlusion 23 (22.3%), and hydrosalpinx 14 (13.6%). Longer infertility duration (≥4 years) significantly correlated with abnormal findings (87.5% vs. 69.1%; p=0.042). Conclusion: HSG revealed a high frequency of tubal and uterine abnormalities, particularly among secondary infertility patients. Early evaluation via HSG can facilitate timely diagnosis and management, potentially improving reproductive outcomes.